2014
DOI: 10.7567/apex.8.012102
|View full text |Cite
|
Sign up to set email alerts
|

Deep-red persistent luminescence in Cr3+-doped LaAlO3perovskite phosphor for in vivo imaging

Abstract: We report deep-red long-lasting persistent luminescence in Cr3+-doped LaAlO3 perovskite phosphor synthesized by solid-state reaction. The LaAlO3:Cr3+ sample showed persistent luminescence peaking at a very long wavelength of 734 nm due to Cr3+:2E → 4A2 transition after ultraviolet excitation. The Sm3+ ion was found to be a good codopant for increasing the persistent luminescence intensity more than 35-fold. For the Cr3+–Sm3+-codoped LaAlO3 sample, the radiance of persistent luminescence in mW sr−1 m−2 unit was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 31 publications
(42 reference statements)
2
46
0
Order By: Relevance
“…Cr 3+ activated LaAlO 3 compound shows zero phonon lines (R-line, 2 E→ 4 A 2 transition) at 734 nm at longer wavelength compared with other well-known Cr 3+ activated oxides, for instance 694 nm in Al 2 O 3 and in ZnGa 2 O 4 . This nature is due to the small Racah parameters of Cr 3+ in this perovskite structure [10,11]. In previous study, we reported that LaAlO 3 :Cr 3+ phosphors show deep-red persistent luminescence after UV light excitation.…”
Section: Introductionmentioning
confidence: 81%
“…Cr 3+ activated LaAlO 3 compound shows zero phonon lines (R-line, 2 E→ 4 A 2 transition) at 734 nm at longer wavelength compared with other well-known Cr 3+ activated oxides, for instance 694 nm in Al 2 O 3 and in ZnGa 2 O 4 . This nature is due to the small Racah parameters of Cr 3+ in this perovskite structure [10,11]. In previous study, we reported that LaAlO 3 :Cr 3+ phosphors show deep-red persistent luminescence after UV light excitation.…”
Section: Introductionmentioning
confidence: 81%
“…In the present work, manganese doped perovskite lanthanide aluminates (LaAlO 3 ) were synthesized by a high-temperature solid-state reaction method, similar to other reported work [19,24,25] and the persistent luminescence behavior was optimized. In order to improve the near-infrared persistent luminescence intensity of LaAlO 3 :Mn 4+ phosphors, a series of samples were prepared using solid state reaction in air through co-doping with a variety of ions with different valence states.…”
Section: Introductionmentioning
confidence: 91%
“…Among the different possibilities, we can cite preliminary works on perovskites reported by Tanabe and co-workers 145 and works concerning PLNPs emitting in the second transparency window reported by Ueda and co-workers 146 and Pan and co-workers 147. A limit with current probes is their long term chemical stability in vivo .…”
Section: Discussionmentioning
confidence: 99%